Koncepcja aktów wewnętrznych w PRL – rozważania nad sytuacją jednostki w systemie autorytarnym - Mielczarek-Mikołajów, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article conseders the legislative activity of state authorities in the period of the Polish People’s Republic, especially in relation to internal law acts. It should be remembered that legislative activity was subjected to the principle of uniform state authority at that time, and the very concept of both internal acts and the entire system of sources of law was regulated in the Constitution of 9 July 1952 quite concisely, which favored the expansion of the subjective and content scope of these acts. For this reason, the objectives and research questions of this study were focused on the analysis of the impact of their uncertainty on the legal situation of an individual: was it direct or only indirect? The considerations presented led the author to the conclusion that internal law was treated instrumentally by state authorities, which caused uncertainty of the legal situation of an individual and the inability to build their legal security. For this reason, during the political transformation, there was a discussion aimed at eliminating the controversies underlying the construction of the system of sources of law in the times of the Polish People’s Republic. To achieve the presented goals and research questions, analytical primarily-dogmatic and legal-comparative methods were used. It should also be remembered that this study does not have only historical value, because although it is based on the consideration of the issuance of legal acts on a specific example, i.e. the Polish People’s Republic, its basic goal is to take a closer look at the legal situation of an individual in the authoritarian model, which is still in force in some contemporary countries. The danger of the return of this system in the case of the Republic of Poland has also been signaled many times in political discussions and debates.
Keywords: akt prawa wewnętrznego; Konstytucja PRL; refleks zewnętrzny; uchwała; zarządzenie; system autorytarny